2010
DOI: 10.1074/jbc.m110.154021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrostatics on the Marginal Cooperativity of an Ultrafast Folding Protein

Abstract: Proteins fold up by coordinating the different segments of their polypeptide chain through a network of weak cooperative interactions. Such cooperativity results in unfolding curves that are typically sigmoidal. However, we still do not know what factors modulate folding cooperativity or the minimal amount that ensures folding into specific three-dimensional structures. Here, we address these issues on BBL, a small helical protein that folds in microseconds via a marginally cooperative downhill process (Li, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 53 publications
6
28
0
Order By: Relevance
“…2 B) approaching the native-state basin. We observe side-chain van der Waals contacts between the N-and Cterminals, most importantly between Ser 3 and Pro 4 at the N-terminal and Leu 38 , Ala 39 , and Lys 40 at the C-terminal, but no hydrogen bonding is seen. From Steps 15 to 16 of Path I, the end-to-end distance sharply rises to above the native value.…”
Section: End-to-end Distancementioning
confidence: 83%
See 1 more Smart Citation
“…2 B) approaching the native-state basin. We observe side-chain van der Waals contacts between the N-and Cterminals, most importantly between Ser 3 and Pro 4 at the N-terminal and Leu 38 , Ala 39 , and Lys 40 at the C-terminal, but no hydrogen bonding is seen. From Steps 15 to 16 of Path I, the end-to-end distance sharply rises to above the native value.…”
Section: End-to-end Distancementioning
confidence: 83%
“…Biophysical Journal 100(10) 2457-2465 coexist under the same conditions. Recent experimental and computational studies have shown that pH and salt concentrations can modulate the folding cooperativity of BBL (39) and the native structure changes with solvent conditions (40). These observations imply that the (free) energy landscape varies with solvent conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies emphasized a relationship between MG and downhill folding (67,91,92), between downhill folding and IDP (12,65,90), and finally between MG and IDP (4, 26, 88, 89, 93, 94). From the energy landscape perspective, the MG state is between the unfolded state at the top of the funnel and the folded state at the bottom of the funnel (78).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most relevant features of surface charge-charge interactions is the Debye-Hückel screening exerted by salt ions that accumulate around surface charges thus strongly weakening electrostatic forces between ionizable residues of the protein (either attractive or repulsive interactions). Accordingly, protein thermodynamic and kinetic stabilities [21] as well as protein folding barriers [26] can be efficiently modulated through electrostatic screening of surface charges. Salt effects on protein stability vary according to their concentration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At low ionic strength (typically below 0.2 M of monovalent salt), salt ions may interact with surface charges of opposite sign causing changes in protein stability that exponentially depend on the ionic strength, even though other mechanisms such as ion specific binding may also be involved. At high ionic strength, salt ions may affect protein stability by perturbing the hydration shell of the protein (which is ion dependent, according to the Hofmeister series) and this effect scales linearly with salt concentration [21, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%